In vitro antifungal susceptibility of griseofulvin, fluconazole, itraconazole and terbinafine against clinical isolates of Trichophyton rubrum and Trichophyton mentagrophytes - Reddy, KR; Reddy, SR (Journal of Universal College of Medical Sciences, 2014)
Investigations on antifungal drug susceptibility were carried out on 90 clinical isolates of Trichophyton rubrum, and Trichophyton mentagrophytes with four antifungal drugs, namely griseofulvin, fluconazole, itraconazole and terbinafine as suggested by National Committee for Clinical Laboratory Standards (NCCLS) M27A (1997) document by broth macrodilution method to standardize in vitro antifungal susceptibility testing and to find out the Minimum Inhibitory Concentration (MIC) of the drugs. In this study, terbinafine was found to be the most efficient drug for all isolates. Terbinafine had the lowest MIC range of 0.001 g/mlto 0.09 g/ml and MIC50 was low at 0.005 g/ml and MIC90 was also low at 0.04 g/ml against T. rubrum; and MIC range of 0.001pg/ml to 0.19pg/ml with a MIC50 of 0.01pg/ml and MIC90 at 0.09 pg/ml against T. mentagrophytes. Itraconazole showed antifungal activity superior to that of fluconazole, with a MIC range of 0.04g/ml to l.56g/ml, with MIC50 at 0.19pg/m land MIC90 at l.56g/ml against T. rubrum; and MIC range of 0.04.g/ml to 1.56pg/ml, with MIC50 at 0.19pg/ml and MIC90 at 0.78pg/ml against T. mentagrophytes. Griseofulvin appears to be still a potent drug for management of dermatophytoses. Griseofulvin had a MIC range of 0.15g/ml to 5.07 g/ml with MIC50 at l.26 g/ml and MIC90 at 2.53 g/ml against T. rubrum; and MIC range of 0.31pg/ml to 5.07pg/ml with MIC50 at 1.26pg/ml and MIC90 at 2.53pg/ml against T. mentagrophytes. Fluconazole showed a high MIC range of 0.19 g/ml to 50 g/ml and MIC50 was high at 1.56g/ml and MIC90 was also high at 12.5 g/ml against T. rubrum; and a high MIC range of 0.09pg/ml to 25.0pg/ml, with MIC50 at 1.56pg/ml and MIC90 at 12.5pg/ml towards T. mentagrophytes. The technique was found to be easy to perform and reliable with consistent results. DOI: http://dx.doi.org/10.3126/jucms.v1i4.9569 Journal of Universal College of Medical Sciences (2013) Vol.1 No.04: 26-28